Stand-alone gas turbine and hybrid MCFC and SOFC-gas turbine systems: Comparative life cycle cost, environmental, and energy assessments - Hasanzadeh, Amirhossein; Chitsaz, Ata; Mojaver, Parisa; Ghasemi, Amir (Energy reports, 2021)
The life cycle cost, environmental, and energy performances of gas turbine (GT) hybridization with two high-temperature fuel cells, solid oxide fuel cell (SOFC) and molten carbonate fuel cell (MCFC), were investigated in detail. The purpose of the present study is to assess the feasibility of the hybridization based on a throughout comparative investigation between 10-MW GT, MCFC-GT, and SOFC-GT systems in their optimum conditions. A model for SOFC, MCFC, and combustion processes was developed using the Gibbs minimization method through Lagrange multipliers. This model calculates unreformed methane during the methane reforming process occurring within the fuel cells. In addition, it calculates pollutant gases emission rates caused by combustion (i.e. NO, NO2, CO2). The economic analysis of the systems was based on the life cycle-costing P1-P2 method which considers fuel and investment costs. The Genetic algorithm was utilized for single- and multi-objective optimization purposes in different cases. Also, a comprehensive sensitivity analysis was conducted to compare the three systems in their optimum conditions to guarantee results obtained from the optimization scenario. The findings revealed that the SOFC was the best candidate for the GT system hybridization. This hybridization reduced the system investment and fuel costs, and CO2 and NO emissions in the fixed power conditions. The maximum energy efficiency of the GT, MCFC-GT, and SOFC-GT systems was obtained to be 43.8%, 53.8%, and 70.3%, respectively. The minimum values for the CO2 emission of the stand-alone GT, the hybrid MCFC-GT, and the hybrid SOFC-GT systems were 460.8 kg/MWh, 367.9 kg/MWh, and 280.4 kg/MWh, besides NO emission was calculated 13.9 kg/MWh, 1.3 kg/MWh, and 1.2 kg/MWh, respectively. The least life cycle cost of the stand-alone GT, the hybrid MCFC-GT, and the hybrid SOFC-GT systems was 163.6, 160.7, and 106 million dollars, respectively. •Fixed 10 MW power of GT, MCFC-GT, and SOFC-GT were compared at optimum conditions.•Life cycle cost of the systems is calculated to predict their economic performance.•SOFC-GT system is 26% and 16% more efficient than GT and MCFC-GT, respectively.•SOFC-GT emits CO2 39% and 24% lower than GT and MCFC-GT, respectively.•SOFC-GT life cycle cost is 35% and 34% lower than GT and MCFC-GT, respectively.